POLA KOMUNIKASI FRESH TEEN COMMUNITY HIPHOP PEKANBARU DALAM MENJAGA KOHESIVITAS - Christian, Robby; Sari, Genny Gustina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The research to see how cohesiveness were build from communication perspective. In this research, I have my focused to Fresh Teen Community. The intention of this research are to reveal communication pattern thai done by The Fresh Teen Community to build a cohesiveness. I using Grup Think theory from Irvin L. Janis as a basic of this research. This theory said that ini cohesiveness were build by a high intensity communication, high enthusiasm of the group members , and they always try to find a consensus as a priority.The method used in this research is descriptive qualitative. Researchers pointed to four key informants and the informants support as resources. To compile the data, researchers using interviews, observation, and documentation study. Be descriptive presentation to answer questions that have been identified previously.Results of this study indicate that the Fresh Teen Community always apply good communication and intensively to build group cohesiveness. Group cohesiveness is evident from the compactness and solidity that exists among the members of the group. The study also revealed that communication had a big role in improving group cohesiveness.